2005
DOI: 10.1093/rpd/nci065
|View full text |Cite
|
Sign up to set email alerts
|

On the roles of the dopants in LiF: Mg,Cu,Na,Si thermoluminescent material

Abstract: In this paper, some results of the study on the roles of the dopants in the LiF:Mg,Cu,Na,Si thermoluminescent (TL) material that was developed at the Korea Atomic Energy Research Institute for radiation protection are presented. Although there have been many studies to investigate the roles of the dopants in LiF:Mg,Cu,P TL material in the TL process, there are some discrepancies in the understanding of the roles of Cu and P between various researchers. In case of LiF:Mg,Cu,Na,Si TL material, there are a few st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 10 publications
0
1
0
Order By: Relevance
“…It was reported [73] that a personnel TL dosimeter using sintered LiF:Mg,Cu,Na,Si TL detector was designed and based on the experimental results of the new dosimeter, it was found appropriate to estimate personnel dose equivalent for wide range energy of photon fields. The results of Lee et al [74] showed that Mg plays a role in the trapping of the charge carriers and Cu plays a role in the luminescence recombination process; however, the effect of Na and Si on the glow curve structure and the TL emission spectra is much less than that of Mg and Cu. It was considered that Na and Si each play a role in the improvement of the luminescence efficiency.…”
mentioning
confidence: 99%
See 3 more Smart Citations
“…It was reported [73] that a personnel TL dosimeter using sintered LiF:Mg,Cu,Na,Si TL detector was designed and based on the experimental results of the new dosimeter, it was found appropriate to estimate personnel dose equivalent for wide range energy of photon fields. The results of Lee et al [74] showed that Mg plays a role in the trapping of the charge carriers and Cu plays a role in the luminescence recombination process; however, the effect of Na and Si on the glow curve structure and the TL emission spectra is much less than that of Mg and Cu. It was considered that Na and Si each play a role in the improvement of the luminescence efficiency.…”
mentioning
confidence: 99%
“…Lee et al [74,78], Kim et al [25] and Tang et al [82,83] studied the emission spectra of LiF doped with various combinations of the dopants: Mg, Cu, P, Si and Na. The measurements and analysis of the three-dimensional TL spectra of Lee et al [74] showed that in LiF:Mg,Cu,Na,Si sample, a 385 nm peak wavelength is observed in the low-temperature range (30-160 o C) and the value of the peak wavelength at the main peak at 210 o C is observed to be ~366 nm, while a 355 nm luminescence is emitted at the high-temperature range (~250 o C). They also report that the emission of LiF:Mg,P is totally different from that observed for LiF:Mg,Cu,P, exhibiting a maximum at ~405 nm.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…The effect of the dopant concentrations on the TL glow curve in LiF:Mg,Cu,Na,Si phosphor was investigated [15,16]. The role of the dopants in TL mechanism for LiF:Mg,Cu,Na,Si phosphor was studied by analysing the TL emission spectra [17][18][19]. However, to the best of our knowledge, up to now, there is almost no work about the evaluation of the trapping parameters and the influence of the heating rate on TL response for LiF:Mg,Cu,Na,Si phosphor.…”
Section: Introductionmentioning
confidence: 99%